Comparison the biodegradation of herbicide pyroxasulfone by some soil bacteria - Kanat, Gurdal (C M B ASSOC, 2018)
The biodegradation of pyroxasulfone (C12H14F5N3O4S), which is the selective herbicide in wheat farming in Turkey is compared with some soil bacteria. These microorganisms were isolated in collected soil samples in Thrace region of Turkey from an agricultural area previously unexposed to pyroxasulfone. The microbial biodegradation of pyroxasulfone was investigated using liquid experiments with identified cultures to determine which of the microorganisms shows best removal performance under agitated culture conditions. The experiments continued about two weeks. Five different apparatuses, were set up and pyroxasulfone in 750 ppm concentration (advised concentration of wheat farmers) was added to each Erlenmayer flasks. Approximately 107CFU/ml of each bacteria added to these flasks. These flasks were shaken at 130rpm at 27 degrees C in sterile conditions for 8 days. Every day, each sample was collected by filtering from flasks and Chemical Oxygen Demand (COD), biochemical oxygen demand (BOD5), total organic carbon (TOC) was determined. As a result of the study, best removal performance observed in Bacillus thuringiensis and Fusarium fujikuroi as 91 and 93% at 7 days in COD, 88 and 83% in BOD5, 90 and 86% in TOC parameters. The lowest performance was seen on Clostridium tetani species for COD, BOD5 and TOC as 55%, 61% and 60% respectively on 7 days. The performance for Bacillus simplex and Bacillus megaterium species occurred between 70% and 80% for these three parameters.
Keywords: Biodegradation; Pyroxasulfone; Chemical oxygen demand; Biochemical oxygen demand; Total organic carbon; CULTURE; SAMPLES; Biochemistry & Molecular Biology; Cell Biology